DIFFERENCES BETWEEN GENERATIONS: THE SUSTAINABLE CHARACTERISTICS OF GENERATION Z - BEJAN BRÎNDUȘA MARIANA; POP CIPRIAN MARCEL (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
Our society's growth and evolution now place a strong emphasis on sustainability. Sustainable practices ensure a brighter future for future generations in a world with finite resources and adverse environmental effects. Of course, everyone's participation is necessary if there is any prospect for a better world. However, with time, studies have revealed that youngsters are more engaged in neighborhood activities, social responsibility initiatives, and sustainable practices. Starting from these considerations, the article aims to outline a profile of Generation Z, taking into account their constant concern for protecting the environment. Thus, we analyze their attitude towards recycling, their behavior distinct from previous generations, and the factors contributing to shaping this behavior. From a methodological perspective, for this research, we conducted a quantitative survey-based study among members of Generation Z. Following the statistical analysis, the results confirmed our hypothesis that young people exhibit proactive behavior, demonstrating a willingness to engage in the life of their community and participate in actions aimed at conserving the environment. Likewise, through this research, we were able to identify the materials most frequently recycled by young people, as well as the significance of the location for recycling.